THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON THE COMPETITIVENESS OF SMALL SCALE INDUSTRIES - Shaikh, Mohammed Sameer (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Earning profits is a common phenomenon of each and every business unit in industry. The foremost goal of any company in any industry is to earn maximize returns with minimal investment in the industry. Companies in any industry have many social obligations to be fulfilled as they have drawn maximum resources from the society. Hence Corporate Social Responsibility has become the catchphrase of millennium across the entire world and the corporate world and even the government must take care of it. The study has focused on the impact of CSR on small scale industries. The study has explored the reasons that motivate small scale industries to involve in corporate social responsibility activities. The study has also highlighted the top healthcare and education projects by CSR. Study has highlighted the benefits and drawbacks of Corporate Social Responsibilities (CSR). For the study qualitative and quantitative data was used and data has been collected by questionnaire method and this research study has collected sample of 100 respondents, 100 respondents from Mumbai region only. It was observed that Corporate Social Responsibility has impact on the competitiveness of small scale industries.